Genehmigungsverfahren klinischer Studien im Bereich der Radioonkologie = Approval procedures for clinical trials in the field of radiation oncology - Simon, Monique; Wenz, Frederik; Debus, Jürgen (Strahlentherapie und Onkologie, 2015)
Background and purposeApplication of ionizing radiation for the purpose of medical research in Germany needs to be approved by the national authority for radiation protection (Bundesamt für Strahlenschutz, BfS). For studies in the field of radiation oncology, differentiation between use of radiation for “medical care (Heilkunde)” versus “medical research” frequently leads to contradictions. The aim of this article is to provide principle investigators, individuals, and institutions involved in the process, as well as institutional review or ethics committees, with the necessary information for this assessment. Information on the legal frame and the approval procedures are also provided.MethodsA workshop was co-organized by the German Society for Radiation Oncology (DEGRO), the Working Party for Radiation Oncology (ARO) of the German Cancer Society (DKG), the German Society for Medical Physics (DGMP), and the German Cancer Consortium (DKTK) in October 2013. This paper summarizes the results of the workshop and the follow-up discussions between the organizers and the BfS.ResultsDifferentiating between “Heilkunde” which does not need to be approved by the BfS and “medical research” is whether the specific application of radiation (beam quality, dose, schedule, target volume, etc.) is a clinically established and recognized procedure. This must be answered by the qualified physician(s) (“fachkundiger Arzt” according to German radiation protection law) in charge of the study and the treatments of the patients within the study, taking into consideration of the best available evidence from clinical studies, guidelines and consensus papers. Among the important parameters for assessment are indication, total dose, and fractionation. Radiation treatments applied outside clinical trials do not require approval by the BfS, even if they are applied within a randomized or nonrandomized clinical trial. The decision-making by the “fachkundigem Arzt” may be supported on request by an opinion given by the DEGRO Expert Committee for clinical trials.ConclusionAn important aim for promoting clinical research and patient care in radiation oncology is to further professionalize planning and implementation of clinical trials in this field. Correct assessment, at an early stage, whether a trial needs to be approved by the BfS may reduce unneccesary costs and reduce the time needed for the approval procedure for those trials which need to be assessed by the BfS.